MEMBANGUN BUDAYA ORGANISASI: INTEGRASI AL-QUR’AN DAN HADIST DALAM PENGELOLAAN PERILAKU ORGANISASI - Nabila, Shofiyyatun; Mutafi, Ali; Trihudiyatmanto, Muhammad; Efendi, Bahtiar (Smart Education, 2025)
Abstract: This article discusses the importance of building an Islamic organizational culture through the integration of Qur'anic and hadith values in organizational behavior management. By adopting the principles contained in the Qur'an, organizations can create a more ethical, fair, and productive work environment. This study uses a qualitative approach with a literature review method to analyze the concepts of Islamic organizational culture and its application in the context of modern management. The results show that the application of Qur'anic and hadith values in organizational culture can improve performance, job satisfaction, and employee loyalty. This article also identifies challenges and strategies in integrating Islamic values into organizational management practices. Keyword: Islamic Organizational Culture, Qur'an, Hadith, Organizational Behavior Abstrak: Artikel ini membahas pentingnya membangun budaya organisasi Islami melalui integrasi nilai-nilai Al-Qur'an dan hadist dalam pengelolaan perilaku organisasi. Dengan mengikuti prinsip-prinsip yang terkandung dalam Al-Qur'an, organisasi dapat menciptakan lingkungan kerja yang lebih etis, adil, dan produktif. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka untuk menganalisis konsep-konsep budaya organisasi Islami dan penerapannya dalam konteks manajemen modern. Hasil penelitian menunjukkan bahwa penerapan nilai-nilai Al-Qur'an dan hadist dalam budaya organisasi dapat meningkatkan kinerja, kepuasan kerja, dan loyalitas karyawan. Artikel ini juga mengidentifikasi tantangan dan strategi dalam mengintegrasikan nilai-nilai Islami ke dalam praktik manajemen organisasi. Kata kunci: Budaya Organisasi Islami, Al-Qur’an, Hadist, Perilaku Organisasi